Cultivating the city in early medieval Italy - Goodson, Caroline (Cambridge : Cambridge University Press, 2021)
Food-growing gardens first appeared in early medieval cities during a period of major social, economic, and political change in the Italian peninsula, and they quickly took on a critical role in city life. The popularity of urban gardens in the medieval city during this period has conventionally been understood as a sign of decline in the post-Roman world, signalling a move towards a subsistence economy. Caroline Goodson challenges this interpretation, demonstrating how urban gardens came to perform essential roles not only in the economy, but also in cultural, religious, and political developments in the emerging early medieval world. Observing changes in how people interacted with each other and their environments from the level of individual households to their neighbourhoods, and the wider countryside, Goodson draws on documentary, archival, and archaeological evidence to reveal how urban gardening reconfigured Roman ideas and economic structures into new, medieval values.
1. Introduction -- 2. Patterns and changes -- 3. The shape of the phenomenon -- 4. Alliances and exchanges -- 5. Values and ideals -- 6. Conspicuous cultivation -- 7. Conclusions.
Title from publisher's bibliographic system (viewed on 08 Mar 2021).
Keywords: Urban gardens -- Italy -- History -- To 1500.; Food supply -- Italy -- History -- To 1500.; Cities and towns, Medieval -- Italy; City and town life -- Italy -- History -- To 1500.; Italy -- History -- 476-1268.; Italy -- Social life and customs -- To 1500.